AAS and spectrophotometric methods for the determination metoprolol tartrate in tablets - Alpdogan, G; Sungur, S (PERGAMON-ELSEVIER SCIENCE LTD, 1999)
Sensitive and specific atomic adsorption spectroscopy (AAS) and spectrophotometric methods have been developed for the determination of beta adrenergic blocking drug, metoprolol tartrate,The method is based on the formation of Cu(II) dithiocarbamate complex by derivatization of the secondary amino group of metoprolol with CS2 and CuCl2 in the presence of ammonia. The copper-bis(dithiocarbamate) complex was extracted into chloroform and the concentration of metoprolol tartrate was determined directly by spectrophotometric and indirectly by AAS measurement of copper. The two methods developed were applied to the assay of metoprolol tartrate in commercial tablet formulations. The methods were compared statistically with each other and with the high performance liquid chromatography (HPLC) method of USPXXII using t- and F-tests. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: metoprolol tatrate; atomic absorption spectrophotometry; UV-VIS spectrophotometry; Spectroscopy